2020
DOI: 10.1002/hon.2764
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeghylated liposomal doxorubicin combination regimen (R‐COMP) for the treatment of lymphoma patients with advanced age or cardiac comorbidity

Abstract: Doxorubicin is the most effective single agent in the treatment of non-Hodgkin's lymphoma (NHL). Its use is limited because of the cardiac toxicity primarily in elderly patients (pts) and in pts with history of cardiac disease. Liposomal doxorubicin has been proven to reduce cardiotoxicity. The aim of this retrospective study was the use of nonpeghylated liposomal doxorubicin (NPLD) in term of efficacy, response rate and incidence of cardiac events. We retrospectively collected the experience of 33 Hematologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…A single consecutive case study looking at the use of dexrazoxane in patients with cardiomyopathy included 2 patients with DLBCL 3 and only recent retrospective analysis of the nonpegylated liposomal doxorubicin combination regimen provides some data on the benefit of its use in patients with lymphoma with cardiac comorbidities, although with little information specific to HF. 4 With respect to the neurohormonal agents in the current study, it found that β-blockers and angiotensin-converting enzyme inhibitors and angiotensin receptor blockers were prescribed in approximately half of the patients at the time of DLBCL diagnosis. While these data may suggest inadequate HF therapy, their interpretation is very limited in the setting of claims database HF ascertainment, lack of ejection fraction data, and clinical information regarding HF symptoms, as well as biomarkers.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…A single consecutive case study looking at the use of dexrazoxane in patients with cardiomyopathy included 2 patients with DLBCL 3 and only recent retrospective analysis of the nonpegylated liposomal doxorubicin combination regimen provides some data on the benefit of its use in patients with lymphoma with cardiac comorbidities, although with little information specific to HF. 4 With respect to the neurohormonal agents in the current study, it found that β-blockers and angiotensin-converting enzyme inhibitors and angiotensin receptor blockers were prescribed in approximately half of the patients at the time of DLBCL diagnosis. While these data may suggest inadequate HF therapy, their interpretation is very limited in the setting of claims database HF ascertainment, lack of ejection fraction data, and clinical information regarding HF symptoms, as well as biomarkers.…”
mentioning
confidence: 67%
“…This pattern is likely a reflection of the lack of dedicated prospective studies of dexrazoxane and liposomal doxorubicin in DLBCL and in patients with preexisting cardiomyopathies, resulting in clinicians’ discomfort in their off-label use. A single consecutive case study looking at the use of dexrazoxane in patients with cardiomyopathy included 2 patients with DLBCL and only recent retrospective analysis of the nonpegylated liposomal doxorubicin combination regimen provides some data on the benefit of its use in patients with lymphoma with cardiac comorbidities, although with little information specific to HF . With respect to the neurohormonal agents in the current study, it found that β-blockers and angiotensin-converting enzyme inhibitors and angiotensin receptor blockers were prescribed in approximately half of the patients at the time of DLBCL diagnosis.…”
mentioning
confidence: 99%
“…At the same time, NPLD might be a valuable therapeutic option to be considered for those patients at moderate/high risk of relapse, which in principle should receive an anthracycline + taxane-based (neo)adjuvant CT, but who are not eligible for conventional anthracyclines due to the presence of cardiac comorbidities. In this perspective, reassuring data from several lymphoma studies highlighted the safety of NPLD in the case of pre-existing cardiac comorbilities [60][61][62][63]. Similarly, in elderly patients, where hypertension, diabetes, coronary artery disease, and cardiac dysfunction (which are all risk factor for anthracyclines' cardiotoxicity) are more frequently present than in younger patients, NPLD might be an option to consider, as also recommended by the International Society for Geriatric Oncology [64].…”
Section: Early-stage Setting Elderly Patients and Main Limitationsmentioning
confidence: 96%
“…The efficacy of these cytotoxic agents is dose-dependent and limited by cardiac tolerability as cardiotoxicity (e.g., cardiomyopathy) is the main adverse effect attributed to anthracyclines (Leonard, Williams, Tulpule, Levine, & Oliveros, 2009). The clinical applications of liposomalassociated anthracyclines either in monotherapy or in combination with other drugs have been well documented by several clinical studies (Schmid et al, 2005;Fridrik et al, 2016;Coltelli et al, 2014;Rigacci et al, 2020). This included reports on maintaining the cytotoxic efficacy whilst minimising cardiotoxicity that permits the use of these chemotherapeutics in broader range of patients with pre-existing cardiopathy.…”
Section: Clinical Applications Of Nanoparticulate Systemsmentioning
confidence: 99%